Antimicrobial activity of metal oxide nanoparticles against Gram-positive and Gram-negative bacteria: a comparative study - Azam, Ameer (Dove Medical Press, 2012)
BACKGROUND: Nanomaterials have unique properties compared to their bulk counterparts. For this reason, nanotechnology has attracted a great deal of attention from the scientific community. Metal oxide nanomaterials like ZnO and CuO have been used industrially for several purposes, including cosmetics, paints, plastics, and textiles. A common feature that these nanoparticles exhibit is their antimicrobial behavior against pathogenic bacteria. In this report, we demonstrate the antimicrobial activity of ZnO, CuO, and Fe(2)O(3) nanoparticles against Gram-positive and Gram-negative bacteria. METHODS AND RESULTS: Nanosized particles of three metal oxides (ZnO, CuO, and Fe(2)O(3)) were synthesized by a sol–gel combustion route and characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, and transmission electron microscopy techniques. X-ray diffraction results confirmed the single-phase formation of all three nanomaterials. The particle sizes were observed to be 18, 22, and 28 nm for ZnO, CuO, and Fe(2)O(3), respectively. We used these nanomaterials to evaluate their antibacterial activity against both Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. CONCLUSION: Among the three metal oxide nanomaterials, ZnO showed greatest antimicrobial activity against both Gram-positive and Gram-negative bacteria used in this study. It was observed that ZnO nanoparticles have excellent bactericidal potential, while Fe(2)O(3) nanoparticles exhibited the least bactericidal activity. The order of antibacterial activity was demonstrated to be the following: ZnO > CuO > Fe(2)O(3).